Case Report: Ovulation Induction in Greater One-Horned Rhinoceros (Rhinoceros unicornis) - Hermes, Robert; Balfanz, Folko; Haderthauer, Simone; Dungl, Eveline; Hildebrandt, Thomas B.; Schwarzenberger, Franz (Frontiers in Veterinary Science, 2021)
Despite a profound knowledge on reproduction biology in greater one-horned (GOH) rhinoceros many individuals cope with sub or infertility or an-ovulatory oestrus. At the same time, early and regular captive breeding is of high importance in female GOH rhinoceros due to their high prevalence to develop genital tract tumours with consequent cessation of reproduction. Thus, mature, an-ovulatory GOH rhinoceros represent a challenge for captive breeding programs and warrant for means of reliable ovulation induction. Here, we used hCG and GnRH analogue histrelin to induce ovulation in an-ovulatory GOH rhinoceros. Upon ultrasound diagnosis of a pre-ovulatory follicle hCG or GnRH were injected to induce ovulation (n=11). As a result, 75% of the hCG (n=6/8) and 33% of GnRH (n=1/3) inductions resulted in ovulation. Ovulation occurred when faecal oestrogen concentration increased before and pregnane concentration after induction. Thirty-six percent of all treatments (n=4/11) failed to induce ovulation. When ovulation induction by hCG or GnRH injection failed oestrogen and pregnane concentrations were significantly lower compared to ovulatory oestrus (P<0.001). Our results suggest that hCG and GnRH analogue facilitate an easily applicable treatment to induce ovulation in females with behavioural but at times an-ovulatory oestrus. Frequent use of hCG as ovulation inducer might help to achieve pregnancies in genetically important but an-ovulatory GOH rhinoceroses.